Memahami Frasa Merendahkan Diri: Kajian Teologis Filipi 2:1-11 dan Implikasinya bagi Jemaat Masa Kini - Helwen Pattikawa; Elsye Yusnengsih; Theofilus Faot; Diniyarti Rara Bolu; Degunias Ton (Visi Sosial Humaniora, 2026)
The humility of Christ is the core of Christian life, yet it is often viewed merely from a doctrinal perspective. This study employs a qualitative approach with a hermeneutical study, specifically exegesis of words and sentences, to explore the deeper meaning of the text. This article aims to understand how the Apostle Paul describes the humility of Christ. The analysis reveals that Christ’s humility conveys significance regarding His identity, soteriology, incarnation, and the omnipotence of God. Therefore, understanding the phrase "the humility of Christ" serves as an exhortation to follow His example.